A Study of Consumer Behaviour Towards Non-Durable Products in The Middle East Region (A Study Focused on Three Different Non-Durable Products Used in Oman, UAE and Bahrain) - Tangarasa Tiburtrious, Andrew Rohanaraj (2016)
Organizations spend quite a lot of their resources to monitor, understand, predict and influence the behaviour of their current and prospective consumers, in order to convince them to buy their products rather than their competitor’s. As such, consumers are bombarded with hundreds of advertisements every day through both traditional and non-traditional media channels. However, effectiveness of such marketing effort will mainly depend on their indepth understanding of the different factors/ variables that influence the consumer purchase decisions. These influencers may vary considerably between durable and non-durable product, due to the amount of time the product is expected to be used by the consumer. These influencers may also differ among different cultures due to variations in risk perception, financial stability, education, attitudes, beliefs and perception. The complexity of the issue requires a detailed research in the area of concern as a clear understanding of these drivers, could be very handy for the Marketing strategists in their planning process. The purpose of this thesis is to gain an in-depth understanding of this exact issue, focusing on the Middle East region. Three countries in the region (Oman, Dubai and Bahrain) and three product groups (washing powder, textiles and footwear) were chosen for this purpose. A standard questionnaire was given to the respondents of all three countries and their responses were noted. The results showed that the degree of influence differs within the product groups, with some of the results not significant at 95% confidence level. The study helped the researcher to clearly identify the primary influencers for each product group. As this is the primary requirement for effective marketing, the findings will be quite handful in arriving at effective marketing decisions, regarding non-durable products in the Middle East region.